KEMITRAAN BIDAN DAN DUKUN DALAM PERTOLONGAN PERSALINAN (Studi Di Puskesmas Galala Kota Tidore Kepulauan) - Norma Jafar; Suryani Kader (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2021)
The purpose of this study was to determine the partnership between midwives and traditional birth attendants in childbirth assistance. Thisstudy was conducted in the working area of the Galala Health Center, Tidore Archipelago City. This study uses a qualitative method, with anethnomethodological approach. The data analysis technique used is the domain data analysis technique. The results of the study indicate that,there are several partnership activities carried out by the Galala Health Center with the community for maternal services and overcoming infantmortality. First, cross-program activities include the KIA Program, Health Promotion Program, Nutrition Program, and ImmunizationProgram. Second, cross-sectoral partnership activities include the North Oba District Government, the Polri and TNI in North Oba District,Urban Village and Village Governments, Posyandu, and community and religious leaders. To maintain a good relationship between the midwifeand the traditional birth attendants, what is being done is to build communication and coordination. Posyandu is used as a formalinstitution for the development and empowerment of traditional birth attendants.